Embedding a Coaching Culture into Programmatic Assessment - Svetlana Michelle King; Lambert W. T. Schuwirth; Johanna H. Jordaan (MDPI AG, 2022)
Educational change in higher education is challenging and complex, requiring engagement with a multitude of perspectives and contextual factors. In this paper, we present a case study based on our experiences of enacting a fundamental educational change in a medical program; namely, the steps taken in the transition to programmatic assessment. Specifically, we reflect on the successes and failures in embedding a coaching culture into programmatic assessment. To do this, we refer to the principles of programmatic assessment as they apply to this case and conclude with some key lessons that we have learnt from engaging in this change process. Fostering a culture of programmatic assessment that supports learners to thrive through coaching has required compromise and adaptability, particularly in light of the changes to teaching and learning necessitated by the global pandemic. We continue to inculcate this culture and enact the principles of programmatic assessment with a focus on continuous quality improvement.